2005
DOI: 10.1111/j.1748-5827.2005.tb00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Myelopathy caused by a histiocytic sarcoma in a cat

Abstract: An eight-year-old, female spayed, domestic shorthair cat presented with a three-week history of progressive general proprioceptive ataxia and upper motor neuron paresis of the hindlimbs. Computed tomography revealed a mediastinal mass invading the vertebral canal with the T1 spinal nerve and roots, causing extramedullary compression of the cranial thoracic spinal cord. Histopathological and immunohistochemical studies of the mass during postmortem examination disclosed a neoplasm, later determined to be a poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
61
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(69 citation statements)
references
References 15 publications
(5 reference statements)
2
61
0
Order By: Relevance
“…Because HS progresses rapidly, the primary and metastatic sites become indistinguishable; therefore, it is difficult to clinically differentiate disseminated HS and MH. These conditions are uncommon in both dogs and cats [1,4,6,7,10,14,15,17,19,21,22]. Here, we report a case of HS in a cat characterized by excessive hemophagocytosis and the presence of splenic masses.…”
Section: Among Histiocytic Malignancies Histiocytic Sarcoma (Hs) Is mentioning
confidence: 93%
See 1 more Smart Citation
“…Because HS progresses rapidly, the primary and metastatic sites become indistinguishable; therefore, it is difficult to clinically differentiate disseminated HS and MH. These conditions are uncommon in both dogs and cats [1,4,6,7,10,14,15,17,19,21,22]. Here, we report a case of HS in a cat characterized by excessive hemophagocytosis and the presence of splenic masses.…”
Section: Among Histiocytic Malignancies Histiocytic Sarcoma (Hs) Is mentioning
confidence: 93%
“…In previously reported cases of HS or MH in cats, the affected animals had nonspecific signs, and the laboratory findings commonly included regenerative or nonregenerative anemia and thrombocytopenia [4,6,7,10,21,22]. Additionally, hemophagocytosis was noted in the spleen, liver and bone marrow in some cases [4,6,7,10].…”
Section: Among Histiocytic Malignancies Histiocytic Sarcoma (Hs) Is mentioning
confidence: 99%
“…Cats, in contrast, are rarely affected by these diseases [6]. Histiocytic sarcoma (HS) in cats has been reported to date in the intestinal wall, femur, tarsus, spleen and liver, and mediastinal and vertebral canals [1,5,11,13,16]. A brief description of an HS in the central nervous system (CNS) of a cat was reported only in a review article [19], while malignant histiocytic disorders have been well demonstrated in the canine CNS [2,4,14,18,20].…”
mentioning
confidence: 99%
“…Phagocytosis and multi-nucleated cells are usually seen, although they are not always prominent features. 2,4,6,[9][10][11][12][13] In this cat, the cytoplasm of the neoplastic cells was scant, there was little evidence of phagocytosis, and multi-nucleated giant cells were rare. Because of the absence of typical morphologic features of HS, immunohistochemistry was used to confirm the diagnosis.…”
mentioning
confidence: 99%
“…9 Histiocytic sarcoma (HS) as a solitary tumor has been rarely described in cats and reports to date include an intramural intestinal mass, a femoral mass, and a mediastinal and vertebral canal HS that resulted in a secondary myelopathy. 2,10,11 A brief description of an HS of the central nervous system of a cat was also included in a review article of intraoperative tumor diagnosis in dogs and cats, but without much clinical detail. 12 To the authors' know ledge, this is the first report of an HS involving the joint of a cat.…”
mentioning
confidence: 99%